Trans influence of ligands on the oxidation of Gold(I) complexes - Yang, Yangyang; Eberle, Lukas; Mulks, Florian; Wunsch, Jonas; Zimmer, Marc; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Journal of the American Chemical Society, 2019)
Gold(I) complexes are considered active species toward oxidative addition; current understanding indicates a different mechanism in contrast to other late transition metals, but a rational understanding of the reactivity profile is lacking. Herein, we propose that the accessibility of the gold(I) center to tri- or tetra-coordination is critical in the oxidative process involving a tri- or tetra-coordinate gold(I) with the oxidizing reagent as one of the ligands as an intermediate. A computational study of the geometry of (Phen)R3PAu(I)NTf2 complexes shows that the accessibility of such tricoordinate species shows a good correlation with the “trans influence” of phosphine ligands: the weak σ-donating phosphine ligands promote tricoordination of gold(I) complexes. The oxidative addition to the asymmetric tricoordinate (Phen)R3PAu(I)NTf2 complexes with alkynyl hypervalent iodine reagents was built. The kinetic profile of the oxidative addition exhibits a good relationship to the Hammett substituent parameter (ρ = 3.75, R2 = 0.934), in which the gold(I) complexes bearing less σ-donating phosphine ligands increase the rate of oxidative addition. The positive ρ indicates a high sensitivity of the oxidative addition to the trans influence. The reactivity profile of oxidative addition to a linear bis(pyridine)gold(I) complex further supports that the oxidative addition to gold(I) complexes is promoted by ligands with small trans influence.